The Impact of Financial Risk and Volatility to the Cost of Debt, and the Average Cost of Capital - Zhukov, Pavel E. (Journal of Reviews on Global Economics, 2018)
The research is devoted to a question – are the price volatility and financial risks the main factors influencing required return on capital. The answer is negative and the outcome is - traditional WACC, based on volatility and capital structure badly describes required return on capital. Then it is poor approximation for discount rate applicable for company cash flows. So, preferable way for practical assessment may be to use projected cash flows and implied stochastic discount rate, calculated by empirical data.